2022
DOI: 10.1021/acschembio.1c00788
|View full text |Cite
|
Sign up to set email alerts
|

Development and Efficacy of an Orally Bioavailable Selective TAK1 Inhibitor for the Treatment of Inflammatory Arthritis

Abstract: Selective targeting of TNF in inflammatory diseases such as rheumatoid arthritis (RA) has provided great therapeutic benefit to many patients with chronic RA. Although these therapies show initially high response rates, their therapeutic benefit is limited over the lifetime of the patient due to the development of antidrug antibodies that preclude proper therapeutic benefits. As a result, patients often return to more problematic therapies such as methotrexate or hydroxychloroquine, which carry long-term side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…At present, no TAK1 targeted therapies have been approved by the FDA, which limits our understanding of how TAK1 inhibition will be tolerated in humans. However, a large body of pre‐clinical work on TAK1 exists 18,29,54–56 . Potential adverse effects could mirror those seen in biological anti‐TNF therapies in which patients have increased risks of opportunistic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, no TAK1 targeted therapies have been approved by the FDA, which limits our understanding of how TAK1 inhibition will be tolerated in humans. However, a large body of pre‐clinical work on TAK1 exists 18,29,54–56 . Potential adverse effects could mirror those seen in biological anti‐TNF therapies in which patients have increased risks of opportunistic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Given the growing number of patients that have become resistant to biologic based anti‐TNF therapies, other molecular targets are being actively explored. Several clinical and non‐clinical studies have shown intracellular elements within TNF and JAK‐STAT3 signaling pathways can be selectively targeted to mitigate the pathogenesis of chronic RA 17–21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scarneo et al [ 110 ] could develop a selective IRAK1 and IRAK4 inhibitor “takinib” which has a high inhibition activity against IRAK 1 and IRAK4 with minimal activity against TAK1 protein. However, takinib is still in the preclinical trial stages and its safety profile is still clinically unknown [ 111 ].…”
Section: Targeting Iraks Represents An Attractive Strategy To Counter...mentioning
confidence: 99%
“…However, most of the available IRAK inhibitors lack selectivity toward IRAKs which may result in different unwanted effects [ 111 ]. Accordingly, lacking selectivity and multiple unwanted effects can affect the decision of prescribing the available IRAK inhibitors in the treatment of COVID-19 disease.…”
Section: Targeting Iraks Represents An Attractive Strategy To Counter...mentioning
confidence: 99%